THE OPTIMUM OPERATION PATTERN OF WAY RAREM RESERVOIR LAMPUNG PROVINCE USING DYNAMIC DETERMINISTIC PROGRAM - FITRIANSYAH (NIM 95006003), HERWAN
Improvement of water required for various development sectors tends to increase in coming. One of effort in management of water resources is development of reservoir to accomodate excess of water in the rains which can be exploited at the time of water shortage in dry season. This thesis present the study of pattern operation of reservoir using optimization technique. Dynamic deterministic program is one of optimization technique applied in operation study of reservoir operation by specifying boundary or rule curve based on critical water conditions namely wet year, normal year and dry year. This thesis evaluated case study at Way Rarem Reservoir which served irrigation in Regency North Lampung, Lampung Province. Result from research using Dynamic determinstic program show the of optimum reservoir operation for the objective function to minimize water shortage may achieved based on the storage elevation montly duration relationship in yearly cycles as presented in the monthly rules curves. In addition the realibility analysis is executed to evaluate the performance of reservoir operation pattern in terms of storage volume dan time services to fulfill irrigation water requirment water use.